THE ANALYSIS OF BANK HEALTH LEVELS USING X-SCORE (ZMIJEWSKI), Y-SCORE (OHLSON), AND Z-SCORE (ALTMAN) (Case Study At Banking Sector In Indonesian Stock Exchange Periods Of 2011-2013) - Mike Widia Wati; . Suhadak; Raden Rustam Hidayat (Fakultas Ilmu Administrasi Universitas Brawijaya, 2015)
This paper examines whether the prediction model of X-Score (Zmijewski), Y-Score (Ohlson), and Z-Score (Altman) are suitable for measuring the financial performance and health level of the listed banks and delisted banks at the Indonesia Stock Exchange. Commonly, there are assumptions about both listed companies and delisted companies that listed companies have good financial performance while delisted companies have a poor financial performance. A company decision to exit from the stock exchange can indeed be caused by the threat of bankruptcy, but the decision can also be by decision to do a merger for sustainability and better company performance. In this study the sample consists of six listed banks and three delisted banks from Indonesia Stock Exchange. Results from this study show that some listed banks are in the gray area during the observation period. The research also indicates that not all listed banks necessarily operate in the conditions of good financial performance. Actually, the results of the used bankruptcy prediction models for delisted banks from the stock exchange show that they were in the safe area category. Conclusively, this study indicates that not all delisted banks from the stock exchanges have a poor financial performance. In fact, the reason that companies delists from the stock exchange could be derived from many reasons, one being that the company chooses consolidate or develop the company business. Keywords: X-Score (Zmijewski), Y-Score (Ohlson), Z-score (Altman), Bank, Bankruptcy